2012
DOI: 10.1007/s00224-012-9421-4
|View full text |Cite
|
Sign up to set email alerts
|

Collusion in Atomic Splittable Routing Games

Abstract: Abstract. We investigate how collusion affects the social cost in atomic splittable routing games. Suppose that players form coalitions and each coalition behaves as if it were a single player controlling all the flows of its participants. It may be tempting to conjecture that the social cost would be lower after collusion, since there would be more coordination among the players. We construct examples to show that this conjecture is not true. Even in very simple single-source-singledestination networks, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…Cominetti et al [12] showed that for games with player-independent affine cost functions an equilibrium can be computed efficiently by solving a quadratic program. For special network topologies (including series-parallel graphs), Huang [32] gave a combinatorial algorithm. For the case of parallel links, Harks and Timmermans [25] gave a polynomial algorithm that computes the equilibrium of an atomic splittable congestion game with player-specific affine costs.…”
Section: Introductionmentioning
confidence: 99%
“…Cominetti et al [12] showed that for games with player-independent affine cost functions an equilibrium can be computed efficiently by solving a quadratic program. For special network topologies (including series-parallel graphs), Huang [32] gave a combinatorial algorithm. For the case of parallel links, Harks and Timmermans [25] gave a polynomial algorithm that computes the equilibrium of an atomic splittable congestion game with player-specific affine costs.…”
Section: Introductionmentioning
confidence: 99%
“…Using two distinct networks with richer architecture than the four‐node network originally displayed by Braess, our second purpose is to ascertain if, and under what conditions, the BP may be realized in the laboratory. Our third and final purpose, which is the primary concern of this article, is to test whether grouping independent flow units into multiple cohorts that operate as unitary decision makers may reduce cost of travel (Huang ). The novelty of our design is that it allows for the first time in such studies testing hypotheses about individual, rather than only aggregate, route choices.…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of single OD (where all the players share the same origin and the same destination), Huang 2013 [14] provides the following example adapted in our language. In the network shown on the left hand side of Figure 2, the social cost at the unique equilibrium with two atomic players of weight 200 and 21 respectively increases when the atomic player of weight 21 deputes her stock to two atomic deputies of weight 20.9 and 0.1 respectively.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Beyond the coalitions formed by nonatomic players, Cominetti et al 2009 [9], Altman et al 2011 [1], and Huang 2013 [14] consider those formed by atomic players. Their results can be interpreted as the impact of certain kinds of collusion and hence, the "inverse" of it, decentralization, on the social cost.…”
Section: Introductionmentioning
confidence: 99%